2006
DOI: 10.1097/01.blo.0000203468.66055.23
|View full text |Cite
|
Sign up to set email alerts
|

Early Internal Fracture Fixation Prevents Bacterial Translocation

Abstract: The aim of our study was to determine whether early internal fixation of major bone fractures helps prevent bacterial translocation in patients with multitrauma. Thirty-seven Sprague-Dawley rats were divided into three groups: (1) anesthesia only (n = 12); (2) the trauma group: tibia and femur fractures and moderate head trauma under anesthesia (n = 14); and (3) the fixation group: fixation of tibia and femur fractures and moderate head trauma under anesthesia (n = 11). After 24 hours, mesenteric lymph nodes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Significant evidence of the disruption of the gastrointestinal (gut) and blood–brain barriers (BBB) has been observed in individuals with neurocognitive impairments, autism, and schizophrenia ( 24 , 42 , 59 , 102 ). Notably, certain conditions that increase the likelihood of delirium are also linked to both increased intestinal permeability and the translocation of LPS or bacteria from the gut into the bloodstream causing tissue damage ( 103 ), bone fracture ( 104 , 105 ), aging ( 106 ), stroke ( 107 ), sepsis ( 108 , 109 ), liver failure ( 110 , 111 ), uremia ( 112 , 113 ), alcohol ( 114 , 115 ), malnutrition ( 116 , 117 ), and psychological stressors ( 118 , 119 ). Furthermore, these risk variables were also linked to BBB disintegration ( 120 127 ), which is considered a prevalent and significant contributing factor to delirium ( 128 ).…”
Section: Discussionmentioning
confidence: 99%
“…Significant evidence of the disruption of the gastrointestinal (gut) and blood–brain barriers (BBB) has been observed in individuals with neurocognitive impairments, autism, and schizophrenia ( 24 , 42 , 59 , 102 ). Notably, certain conditions that increase the likelihood of delirium are also linked to both increased intestinal permeability and the translocation of LPS or bacteria from the gut into the bloodstream causing tissue damage ( 103 ), bone fracture ( 104 , 105 ), aging ( 106 ), stroke ( 107 ), sepsis ( 108 , 109 ), liver failure ( 110 , 111 ), uremia ( 112 , 113 ), alcohol ( 114 , 115 ), malnutrition ( 116 , 117 ), and psychological stressors ( 118 , 119 ). Furthermore, these risk variables were also linked to BBB disintegration ( 120 127 ), which is considered a prevalent and significant contributing factor to delirium ( 128 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, although sanitation has been improved in the hospitals, an equivalent phenomenon of post‐traumatic deaths from systemic infections persists to this day. Recent in vivo studies confirmed the trauma‐associated translocation of endogenous bacteria from the gut following sterile head injury, 6 , 7 indicating another source of PTI.…”
Section: Definitionsmentioning
confidence: 92%
“…This may trigger the translocation of bacteria from the gut to the circulation, and increase the risk of systemic PTI. However, whether PTI and increase gut permeability are directly associated with each other, remains to be investigated 6 , 7 , 92 …”
Section: Immunological Changes Following Sterile Traumamentioning
confidence: 99%
See 2 more Smart Citations